Prevalence of Salmonella Spp. in Backyard Chickens in Paraguay - Leotta, G.; Suzuki, K.; Alvarez, F.L.; Nunez, L.; Silva, M.G.; Castro, L.; Faccioli, M.L.; Zarate, N.; Weiler, N.; Alvarez, M.; Copes, J. (International Journal of Poultry Science, 2010)
The objective of this study was to (1) determine prevalence against Salmonella spp. and (2) investigate the risk factors with the positivity of the pathogens in backyard chickens in Paraguay. The field study was conducted between 31 March and 9 April 2009. A total of 50 smallholder farming households with chickens reared at backyards were initially selected from 25 of 52 administrative districts in San Lorenzo, Central Department, Paraguay. The required sample size of chickens was 400 in total. Data collection through questionnaire interviews about some selected poultry farming practices for each farm, together with cloacal swab sample collections for each chicken was implemented. The swab samples were examined microbiologically. Statistical analyses were used to describe the differences between the two chicken groups categorized according to positivity against Salmonella spp. The overall percentage of test-positive against Salmonella spp. was 3.5% [95% confidence interval (CI): 1.9%-5.7%]. The final logistic regression model indicated that free-range birds were more likely to have positivity against Salmonella spp., compared with caged birds (odds ratio: 3.5, 95% CI: 1.2-10.3).